Application of advanced statistical control for edge bead reduction in laminating process - Fan, Francis Huangjia (2014)
Edge beading is a side effect occurring in the extrusion coating process due to the phenomenon of neck-in. It causes the high edge defect in the finished carton roll after the laminated sheets are wrapped around the core roller; the affected carton sheets do not satisfy the requirement for surface flatness when fed into the beverage filling machines.